Echinochrome A Protects Mitochondrial Function in Cardiomyocytes against Cardiotoxic Drugs - Jeong, Seung Hun (MDPI, 2014)
Echinochrome A (Ech A) is a naphthoquinoid pigment from sea urchins that possesses antioxidant, antimicrobial, anti-inflammatory and chelating abilities. Although Ech A is the active substance in the ophthalmic and cardiac drug Histochrome(®), its underlying cardioprotective mechanisms are not well understood. In this study, we investigated the protective role of Ech A against toxic agents that induce death of rat cardiac myoblast H9c2 cells and isolated rat cardiomyocytes. We found that the cardiotoxic agents tert-Butyl hydroperoxide (tBHP, organic reactive oxygen species (ROS) inducer), sodium nitroprusside (SNP; anti-hypertension drug), and doxorubicin (anti-cancer drug) caused mitochondrial dysfunction such as increased ROS level and decreased mitochondrial membrane potential. Co-treatment with Ech A, however, prevented this decrease in membrane potential and increase in ROS level. Co-treatment of Ech A also reduced the effects of these cardiotoxic agents on mitochondrial oxidative phosphorylation and adenosine triphosphate level. These findings indicate the therapeutic potential of Ech A for reducing cardiotoxic agent-induced damage.